Female Engagement in Asian Workforce: Exploring the Impact of ICT - Duwal, Niroj; Silwal, Shreyeska (Khwopa Journal, 2024)
The labor market in Asian countries has both challenges and opportunities for women to participate in the work force. The aim of this article is to investigate the association of ICT, female education, and fertility with the female labor force participation in 48 Asian countries from 2014 to 2021 in fixed effect model. The results reveal that there is positive and significant association of internet use with female labor force participation, whereas there is a negative relationship between mobile phone usage and female labor force participation which is only significant at ten percent. Similarly, the control variables, GDP and female secondary school enrollment have also positive relationship with female labor force participation. The fertility rate has negative association with female labor force participation. Furthermore, it is found that ICT has significantly affected to female labor participation in Central Asia and South-Eastern Asia. The findings of this article explain that the ICT has increased female labor force participation, their empowerments and returns in the Asian countries. However, it is applicable for the appropriate policies of ICT usage in such a way that it not only increases female labor force participation but also increases the productivity of female workforce. The policy makers should increase the skill-oriented applications in both mobile applications and internet browsers. There should be restrictions on certain applications in the devices which reduce work productivity thereby assuring increase in female labor force participation.